Kajian Yuridis Penggunaan Kecerdasan Artifisial pada Pembuatan dan Penyebaran Konten Pornografi di Media Sosial dalam Hukum Positif Indonesia - Raisa Safina; Khalda Alifia Azzahra; Ananda Fersa Dharmawan (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This journal aims to conduct a juridical study on the use of artificial intelligence (AI) in the creation and dissemination of pornography content on social media, with a focus on Indonesian positive law. The main issues identified involve efforts to regulate the use of AI in pornography from an ethical standpoint and the necessity of appropriate regulations. The research has two main objectives: first, to identify the risks arising from the misuse of AI in creating pornography content and find ways to address these risks; second, to analyze the appropriate legal regulations regarding the use of AI to address the creation and dissemination of pornography content on social media, as well as to study regulations applied by some countries regarding AI use. The research findings indicate the positive impact of AI in various aspects of life, but its use in pornography production poses negative effects that require regulation. In Indonesia, regulations are limited to specific types of AI, necessitating updates to protect society from potential misuse of AI technology.